Transformational Leadership and Contextual Performance: A Quantitative Study among Nursing Staff in Kuala Lumpur - Manesh, Mandana Heshmati; Singh, Jugindar Singh Kartar; Hussain, Ibiwani Alisa Binti (International Journal of Management and Sustainability, 2018)
The role of nurses in the health care sector is critical and the demand for nurses in Malaysia is expected to reach 130,000 qualified nurses by 2020. This paper investigated the influence of transformational leadership on contextual performance of nurses in Kuala Lumpur. Past research revealed that employee sustainable performance is positively influenced by transformational leadership. However, there is a dearth of studies on the relationship between transformational leadership and employees’ contextual performance in the nursing sector in Kuala Lumpur. The present study attempts to fill the research gap by investigating the influence of intellectual stimulation, individualized consideration, inspirational motivation and idealized influence towards better contextual performance This was a quantitative research and data was gathered through self-administered questionnaires from 135 nurses in Kuala Lumpur. The SPSS software was used, and the findings revealed that intellectual stimulation, individualized consideration, inspirational motivation and idealized influence had a positive correlation with contextual performance. The findings suggest that the four dimensions are interdependent, and they harmonize to yield better contextual performance. The findings of this study have practical implications in nursing leadership. Transformational leadership enables leaders in the nursing sector to motivate nurses and implement change effectively. This study is one of very few studies which have investigated the effect of transformational leadership on employee’s contextual performance in the nursing sector in Kuala Lumpur. The results of this study will add to the current body of knowledge plus assist in creating foundational solutions to improve performance of nurses.